ANIMAL TALES IN CHEROKEE AND SUMBAWA TRADITION: A STUDY ON CHEROKEE AND SUMBAWANESE VALUES REFLECTED IN THREE PAIRS OF STORIES - Vivin Nila Rakhmatullah (Universitas Gadjah Mada, 2014)
The purpose of this article is to observe a comparative study of animal tales of Cherokee, one of Native American tribes and Sumbawa, an Indonesia tribe, especially to describe the similarities and the differences in delivering moral values between the three pairs of tales, to explore the cultural values in Cherokee and Sumbawa animal folktales, and to elucidate the representation of the characters in those animal folktales. The animal tales of Cherokee are How the Terrapin Beat the Rabbit, The Rabbit and The Possum Seek a Wife, and How the Deer Got His Horns. While, the animal tales of Sumbawa are: The Tales of The Monkey, The Turtle and The Snail, The Tales of The Monkey And The Flamingo and The Cocky Monkey (Sruduk Team). The animal characters in these tales are to represent human being, their characteristics, moral and cultural values. Their main characters in most of animal tales are different; Cherokee is represented by the character of Rabbit, whereas Sumbawa is represented by the character of Monkey. The animal tales of Cherokee and Sumbawa is very much alive and imbued with power to create identity and community.